Coaching dynamics in elite volleyball: The role of a need-supportive and need-thwarting coaching style during competitive games - Morbée, S.; Haerens, L.; Soenens, B.; Thys, J.; Vansteenkiste, M. (Psychology of Sport and Exercise, 2024)
Grounded in Self-Determination Theory, this game-to-game study among Flemish volleyball coaches and athletes had two primary objectives. First, we examined how variations in need-supportive and need-thwarting coaching styles related to variations in athletes` basic psychological needs, motivation, and coach-rated performance. Second, we examined whether athletes who perceived their coach as need-thwarting during a specific game would experience different outcomes based on the overall need-supportive or need-thwarting coaching style they encountered across games. Linear mixed modeling on data from 190 elite volleyball athletes (Mage = 23.95, 32.6% male) and their 26 coaches (Mage = 48.12, 95.7% male) indicated positive associations between game-specific need-supportive coaching and athletes` reports of game-specific basic psychological need experiences and motivation, as well as coach-rated performance, whereas game-specific need-thwarting coaching showed opposite trends. Athlete perceptions of a coaching style were more predictive of the outcomes than coach perceptions. Second, the lack of systematic cross-level interactions between game-specific coaching and team-level coaching indicated that the observed correlates of game-specific need-thwarting and need-supportive coaching hold regardless of the perceived overall need-thwarting or need-supportive style of the coach across games.